Consciousness and Personhood in Medical Care - Blain-Moraes, Stefanie; Racine, Eric; Mashour, George A. (Frontiers in Human Neuroscience, 2018)
Current paradigms in Western medicine often fail to differentiate clearly between consciousness, responsiveness and personhood. The growing number of individuals who exist with sustainable cardiopulmonary systems but who are behaviorally unresponsive has prompted a cultural reconsideration of the relationship between the presence of consciousness and what it means to be a person. This article presents relevant clinical situations that exemplify the different modes in which personhood and consciousness can be associated and dissociated: disorders of consciousness, emergence from anesthesia, and neocortical death. We draw from these examples to call for a reflection on and possible revision of the dominant approach towards unresponsive persons to one in which care providers may work from the default assumption of the existence of an individual’s personhood as part of their therapeutic intervention. Behavior consistent with this assumption aligns with the principle of respect for persons in the face of the uncertainty created by the high rate of misdiagnosis of unconsciousness in unresponsive patients and is most consistent with a therapeutic approach to care considering evidence suggesting that attributing personhood may in fact evoke consciousness in these patients.